2008
DOI: 10.1186/1477-7819-6-74
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and gastroesophageal reflux disease

Abstract: Background: The nature of the relationship between Helicobacter pylori and reflux oesophagitis is still not clear. To investigate the correlation between Helicobacter pylori infection and GERD taking into account endoscopic, pH-metric and histopathological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
4
26
0
8
Order By: Relevance
“…Indeed, some reports have demonstrated that H. pylori serostatus had an inverse association with GERD [11-13, 33, 35-38]. Other reports, however, contradict such a relationship [7,8,39]. The present study confirmed the significant protective role of H. pylori infection against EE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, some reports have demonstrated that H. pylori serostatus had an inverse association with GERD [11-13, 33, 35-38]. Other reports, however, contradict such a relationship [7,8,39]. The present study confirmed the significant protective role of H. pylori infection against EE.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, delineating the risk factors for GERD in an asymptomatic general population has great clinical implications. Disturbance of the antireflux barrier system, consisting of the lower esophageal sphincter, is the main mechanism involved in the pathophysiology of GERD [7]. Other underlying conditions, such as gastric acid production, intragastric pressure, and esophageal acid exposure, are also recognized as important factors [8][9][10][11] complicating the pathophysiological pathways involved in GERD.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, several studies have suggested that H. pylori is also involved in the development of coronary heart disease [5], idiopathic thrombopenic purpura [6] and gastroesophageal refl ux disease [7]. H. pylori is a major cause of illness and death worldwide [4]; therefore, eradication of H. pylori has become an important consideration in the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries H. pylori infection is much higher (90%). There are some virulence factors that enables H. pylori to be "implanted" and then to be persisted in host body (Grande M, 2008). Most of H. pylori strains develop VacA cytotoxin that has the ability to be vacuolated.…”
Section: Introductionmentioning
confidence: 99%